Hormonal Programming Across the Lifespan - Nugent, B. M.; Tobet, S. A.; Lara, H. E.; Lucion, A. B.; Wilson, M. E.; Recabarren, S. E.; Paredes, A. H. (Hormone and Metabolic Research, 2012)
Hormones influence countless biological processes across an animal’s lifespan. Many hormone-mediated events occur within developmental sensitive periods, during which hormones have the potential to cause permanent tissue-specific alterations in anatomy and physiology. There are numerous selective critical periods in development with different targets being affected during different periods. This review outlines the proceedings of the Hormonal Programming in Development session at the US-South American Workshop in Neuroendocrinology in August 2011. Here we discuss how gonadal steroid hormones impact various biological processes within the brain and gonads during early development and describe the changes that take place in the aging female ovary. At the cellular level, hormonal targets in the brain include neurons, glia, or vasculature. On a genomic/epigenomic level, transcription factor signaling and epigenetic changes alter the expression of critical hormone receptor genes across development and following ischemic brain insult. In addition, organizational hormone exposure alters epigenetic processes in specific brain nuclei and may be an important mediator of sexual differentiation of the neonatal brain. Brain targets of hormonal programming, such as the paraventricular nucleus of the hypothalamus, may be critical in influencing the development of peripheral targets, such as the ovary. Exposure to excess hormones can cause abnormalities in the ovary during development leading to polycystic ovarian syndrome (PCOS). Exposure to excess androgens during fetal development also has a profound effect on the development of the male reproductive system. In addition, increased activity of the sympathetic nerve and stress during early life have been linked to PCOS symptomology in adulthood. Finally, we describe how age-related decreases in fertility are linked to high levels of nerve growth factor (NGF), which enhances sympathetic nerve activity and alters ovarian function.
Keywords: gonadal hormones; development; aging; brain; ovary; stress